2016
DOI: 10.1037/abn0000097
|View full text |Cite
|
Sign up to set email alerts
|

Attention-deficit/hyperactivity disorder developmental trajectories related to parental expressed emotion.

Abstract: Background In the transition from childhood to adolescence, attention-deficit/hyperactivity disorder (ADHD) developmental trajectories diverge. Family environment, as indexed by parental expressed emotion, may moderate these trajectories. Methods 388 children with ADHD and 127 control children were assessed using a multi-informant, multi-method diagnostic procedure at up to three time points one year apart in an accelerated longitudinal design spanning ages 7-13 years. Latent-class growth analysis (LCGA) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 49 publications
7
37
0
1
Order By: Relevance
“…These associations were robust for the total sample, but particularly amongst boys. The measure used specifically captures negative evaluations from their parents, demeaning attitudes and perceived threat, which is consistent with recent findings in which parents' negative expressed emotion about their children predicted a persistent ADHD trajectory [44]. Nevertheless, findings on parental expressed emotion and hostility in relation with ADHD are mixed, with reports of negative findings [45]; others have found that children's ADHD may precede [46] or evoke [47] parental hostility.…”
Section: Associations With Maltreatment: Emotional and Physical Abusesupporting
confidence: 77%
See 1 more Smart Citation
“…These associations were robust for the total sample, but particularly amongst boys. The measure used specifically captures negative evaluations from their parents, demeaning attitudes and perceived threat, which is consistent with recent findings in which parents' negative expressed emotion about their children predicted a persistent ADHD trajectory [44]. Nevertheless, findings on parental expressed emotion and hostility in relation with ADHD are mixed, with reports of negative findings [45]; others have found that children's ADHD may precede [46] or evoke [47] parental hostility.…”
Section: Associations With Maltreatment: Emotional and Physical Abusesupporting
confidence: 77%
“…Further, both parental behaviours [52] and physical abuse [53] have been shown to moderate genetic vulnerability for ADHD. Meanwhile, low maternal warmth [54] and frequent parental criticism [44] have been recently related with a worse ADHD symptom trajectory.…”
Section: Potential Mechanisms Explaining Adhdmaltreatment Associationsmentioning
confidence: 99%
“…Hyperactive children who experienced effective parenting did not progress to more severe externalizing outcomes, whereas those who experienced explosive, coercive, and nattering parenting did. High rates of parental criticism also mediate associations between ADHD and growth in ODD among 7-13-year-olds (Musser et al 2016). Similar to research on temperament referred to above, disruptions in parenting that are common to maternal depression mediate longitudinal associations between ADHD in early childhood and conduct problems 2-8 years later, whereas positive parenting offers protection (Chronis et al 2007).…”
Section: Ineffective Parenting and Coercive Family Processesmentioning
confidence: 58%
“…High emotional expression in parenting (particularly negative-reactive instead of positive parenting strategies) was associated with ADHD54 as well as higher rates of aggressive behavior, fighting, and later impulsivity 55. Similarly, research has found a direct correlation with the behaviors and parenting roles in time perspective studies.…”
Section: Correspondence In Lifestyles Of Adhd and Present Hedonistic mentioning
confidence: 92%